Silicon-Quantum-Dot Light-Emitting Diodes With Interlayer-Enhanced Hole Transport - Wei Gu; Xiangkai Liu; Xiaodong Pi; Xingliang Dai; Shuangyi Zhao; Li Yao; Dongsheng Li; Yizheng Jin; Mingsheng Xu; Deren Yang; Guogang Qin (IEEE Photonics Journal)
Despite the technological importance of silicon quantum dots (Si QDs) which are solely made of abundant and nontoxic Si, Si-QD light-emitting diodes (LEDs) clearly lag behind those based on other QDs, especially Cd- or Pb-containing QDs. It is imperative that novel measures should be taken to boost the performance of Si-QD LEDs. Here, we demonstrate that Si-QD LEDs can work much more efficiently after the use of interlayers between indium tin oxide (ITO) and poly(ethylene-dioxythiophene):polystyrene sulphonate (PEDOT:PSS) to enhance the hole transport of the devices. The interlayer of dipyrazino (2, 3-f:2 ′, 3 ′-h) quinoxaline-2,3,6,7,10,11-hexacarbonitrile (HAT-CN) or MoO3 increases the work function of ITO and improves the band alignment, leading to better hole injection from ITO to PEDOT:PSS. The resulting mitigated charge unbalance causes both the external quantum efficiency (EQE) and stability of Si-QD LEDs to significantly increase (up to ∼170% for EQE and ∼240% for device half-lifetime). The highest EQE of ∼2.4% obtained in the current work is among the best values that have been reported for Si-QD LEDs. Even without encapsulation, the device half-lifetime is up to ∼8.5 h. The enhancement of the hole transport induced by MoO3 is more significant than that induced by HAT-CN. Therefore, MoO3 more significantly enhances the performance of Si-QD LEDs than HAT-CN.